Simultaneous forequarter amputation and radical mastectomy for metastatic breast carcinoma in a male patient: a case report - Ayvaz, Mehmet (The Korean Surgical Society, 2011)
Although the majority of forequarter amputations are performed for high-grade bone and soft tissue sarcomas or extensive osteomyelitis of the upper extremity, this radical operation may also be indicated for the curative treatment of recurrent breast cancer and for the palliation of locally advanced breast cancer. We report a male patient with metastatic breast adenocarcinoma who underwent simultaneous mastectomy and forequarter amputation for the management of both his primary and metastatic disease.